DAMPAK ADEGAN KEKERASAN FILM KARTUN BOBOIBOY TERHADAP PERILAKU AGRESIF ANAK DI DESA BUNTU BATUAN KECAMATAN MALUA KABUPATEN ENREKANG (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This research discusses the impact of the Boboiboy cartoon film scene on children's aggressive behavior in Buntu Batuan Village, Malua District, Enrekang Regency. The aim of this research is to determine the impact of violent scenes in the Boboiboy cartoon film on the aggressive behavior of children in Buntu Batuan Village, Malua District, Enrekang Regency, and also to determine parents' efforts to deal with and overcome this aggressive behavior. This type of research is qualitative with a communication approach, and the informants in this research are parents and children (5–10). Data collection methods include interviews and documentation. Data processing and analysis techniques use the Miles and Hubrman model, which is carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this research show that violent scenes in the cartoon film Boboiboy have an impact on the aggressive behavior of children in Buntu Batuan Village, Malua District, Enrekang Regency, such as fighting with their friends or siblings, chasing them on the highway where there are lots of vehicles passing by. The positive impacts of cartoon films include: 1) Can improve children's memory, imagination and creativity. 2) Increase self-confidence and foster children's social values. 3) Increase children's vocabulary and foreign languages. while the negative impacts include: 1) Children behaving aggressively. 2) behaving inattentively or unfocused and like to procrastinate. 3) Speaks impolite language and likes to get angry. 4) Lazy to study. The efforts made by parents in dealing with and overcoming aggressive behavior include giving advice, giving examples or explaining scenes in cartoons when children are watching, as well as regulating the hours children watch television. The implications of this research can be used as information and consideration for future researchers who wish to conduct more in-depth research on the same topic. As input for parents to pay more attention and control what they watch and provide an understanding of the scenes shown on television to their children.